Proceedings of the 8th International Conference on Interaction Design and Children 2009
DOI: 10.1145/1551788.1551825
|View full text |Cite
|
Sign up to set email alerts
|

User-oriented design and tangible interaction for kindergarten children

Abstract: This paper describes a tabletop prototype that allows kindergarten children to take the benefits of the new pedagogical possibilities that tangible interaction and tabletop technologies offer to manipulative learning. After analyzing children's cognitive and psychomotorial skills, we have designed and tuned a prototype game suitable for children aged 3 to 4 years old. Our prototype uniquely combines low cost tangible interaction and tabletop technology with tutored learning. The design has been based on observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…This extends prior work (e.g. Marco et al [15]) that associates the presence and position of virtual characters with that of tangible tokens. Specifically, it moves beyond these past efforts in its consideration of how a puzzle piece metaphor can be leveraged to create richer and more sophisticated mappings and relationships between and among the virtual contents and physical tokens.…”
Section: The Digital Dream Labsupporting
confidence: 83%
See 2 more Smart Citations
“…This extends prior work (e.g. Marco et al [15]) that associates the presence and position of virtual characters with that of tangible tokens. Specifically, it moves beyond these past efforts in its consideration of how a puzzle piece metaphor can be leveraged to create richer and more sophisticated mappings and relationships between and among the virtual contents and physical tokens.…”
Section: The Digital Dream Labsupporting
confidence: 83%
“…Most fundamentally, it needed to express the link between manipulations of the puzzle pieces and the on-screen content. Unsurprisingly, the studies showed that this was best achieved via a tight coupling of the physical and virtual contents (as noted in [15]). However, the studies also stressed the value of visibility of the underlying working principles of the system.…”
Section: Iterative Design and Formative User Studiesmentioning
confidence: 98%
See 1 more Smart Citation
“…Here research seeks to explore the idea generation process [20] or to consider how PD can be used with specific user groups or specific design challenges [32]. User groups that have been shown to be able to participate in design activities include very young children [17] and teenagers [19].…”
Section: Pd With Childrenmentioning
confidence: 99%
“…Here research seeks to identify methods by which ideas can be generated, as in the mixing ideas approach found in (Guha et al, 2004) or to explore the idea generation process (Mazzone, Read, & Beale, 2008b) or to consider how PD can be used with specific user groups or specific design challenges. User groups that have been shown to be able to participate in design activities include very young children (Marco, Cerezo, Baldasarri, Mazzone, & Read, 2009) as well as teenagers (Mazzone, Read, & Beale, 2008a). Products for which participatory design has been shown to work have primarily been functional products including web sites (Read et al, 2002) and digital libraries (Theng et al, 2000).…”
Section: Related Workmentioning
confidence: 99%